Analysis to the Error and Accuracy of Differential Barometric Altimetry - Lirong Zhang; Zhengqun Hu (Institute of Advanced Engineering and Science, 2014)
The traditional barometric altimetry acquired the absolute height has poor precision mainly because of the climate and weather, gravity and temperature effect on atmospheric pressure. By introducing reference point correction into barometric altimetry can improve the accuracy of the height being measured and extend its application range since the error caused by slow variation of atmospheric pressure and temperature is eliminated. Users receive the meteorological data from barometric reference stations and calculate the local height through local measurement by high precision. To begin with, this paper describes the principle and mathematical model of differential barometric altimetry. And then analyze the main factors influence to the precision of differential barometric altimetry. Finally, accuracy and error of the method is to be analyzed in detail.